UPAYA PENGEMBANGAN PENGELOLAAN PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) - RB SUHARTA (LPPM UNY, 2003)
Abstract This study aimed to investigate management of community learning activity center (PKBM), obstacles and its developing efforts in order to be usable for solving problems faced by PKBM. The qualitative study was carried out on PKBM located in Pajangan sub district, Bantul Yogyakarta. PKBM was taken purposively as study subject. Data was collected by interview and documentation technique. Then the data were analyzed by classifying it into units and then categorized and interpreted. Community learning activity center as implementation of community-based education and as a place to learning people need optimal management that done continuously. Some characteristics of PKBM are decision making thjat most of them done by people including aspects of planning, organization, motivation, controlling, and evaluation on all learning program implementationas form of its management. Result of the study indicated that (1) planning aspect on learning people, tutor, facility, fund, study program and relation